Masked Panji plays in nineteenth-century Java; The story of Kuda Narawangsa - Brakel-Papenhuyzen, Clara (Wacana, Journal of the Humanities of Indonesia, 2020)
This article discusses the Javanese Panji-story Kuda Narawangsa, which I first watched as a masked performance in a village south of Yogyakarta in 1977. The play featured Galuh Candra Kirana, spouse of Prince Panji of Jenggala, in the masculine form of “Kuda Narawangsa”. Historical information on this play in archival manuscript sources, found mainly in the collections of Leiden University Libraries, proves that it was well-known in Java during the nineteenth century. In this article, descriptions of performances in manuscripts or printed publications are combined with historical play-scripts (pakem) from Surakarta and Yogyakarta, which have not been investigated so far. Special attention is paid to the script of a masked performance of the Kuda Narawangsa story in a manuscript from the Mangkunegaran palace, investigating what this historical pakem can tell us about the meaning and context of a masked performance of this story in nineteenth century Java. A story which according to recent publications remains relevant in Indonesian society to this day.